Optimization of Carbopol 940 and Glycerol Concentration in Antioxidant Gel of Alstonia scholaris L. Leaf extract with Simplex Lattice Design Method - Pratiwi, Puspa Dwi (Indonesian Journal of Cosmetics, 2023)
Alstonia scholaris L. contains several compounds, which has been proven to be potential as skin protection by formulating in gel preparation. The aims of this study was to obtained the concentration of carbopol 940 and glycerol to produce an optimal gel preparation of Alstonia scholaris L. leaf extract. Simplex lattice design was used as optimization method with two independent variable, carbopol 940 (0.5%-2.5%) as gelling agent and glycerol (14%-16%) as humectant. There were 5 formulas carried out to physical properties evaluation: organoleptic, homogeneity, spreadability, pH, adhesion time and viscosity. The result showed that the prediction of optimal formula from SLD method with 1.67% carbopol 940 and 14.83% of glycerol. The physical properties of optimal formula was 5.206±0,125 of pH value; 28,768.24±4,608.11 cP of the viscosity value; 5.96±0,087 cm of spreadability value; and 55.146±1.174 seconds of adhesion. There was no significant difference of SLD prediction responses with observation respons.